Burnout syndrome and workplace violence among nursing staff: a cross-sectional study - Tsukamoto, Sirlene Aparecida Scarpin; Galdino, Maria José Quina; Barreto, Maynara Fernanda Carvalho; Martins, Júlia Trevisan (São Paulo Medical Journal, 2022)
BACKGROUND: Among healthcare professionals, nursing workers are the most prone to becoming victims of workplace violence and present the highest burnout levels. OBJECTIVES: To investigate the association between burnout syndrome and workplace violence among nursing workers. DESIGN AND SETTING: Cross-sectional study carried out at a teaching hospital in southern Brazil. METHODS: This study involved 242 nursing workers. We collected data over a six-month period using a sociodemographic and occupational survey, the Survey Questionnaire Workplace Violence in the Health Sector and the Maslach Burnout Inventory – General Survey. For occupational violence, we selected the Survey Questionnaire Workplace Violence in the Health Sector. Burnout syndrome was evaluated using the Maslach Burnout Inventory – General Survey. The data were analyzed in the Statistical Package for the Social Sciences (SPSS). Categorical variables were described as absolute and relative frequencies and numerical variables in terms of central trend and dispersion measurements. For data analysis, we applied descriptive statistics and multiple logistic regression. RESULTS: The multiple models indicated that the workers who had experienced verbal abuse, physical violence and concern about workplace violence over the past 12 months had significantly higher chances of presenting high emotional exhaustion (P < 0.05) and depersonalization (P < 0.05) and low professional accomplishment (P < 0.05). CONCLUSION: Occurrence of violence significantly increased the chances of great emotional exhaustion and depersonalization and low professional achievement, within burnout syndrome. Therefore, workplace violence prevention strategies need to be put in place to provide workers with a safe workplace in which to conduct their activities.